The role of stereotactic body radiation therapy in the treatment of colorectal liver metastases - Marinkovic, Mladen; Stojanovic-Rundic, Suzana (Medicinski podmladak, 2022)
Colorectal cancer is third most common malignant disease and second leading cause of cancer-related deaths worldwide. In Serbia in 2020 there were 5900 new cases and around 3300 number of deaths related to this disease. Metastatic disease is most frequently located in liver.  Surgery is first option if complete resection of liver metastases is achievable. Since liver metastases are resectable in 10-20% of cases there is a possibility of implementation of other treatment modality. Alteranative for surgery in local treatment of unresectable metastases are stereotactic body radiation therapy (SBRT), interstitial and intraluminal brachytherapy, transarterial chemoembolization, hepatic arterial infusion chemotherapy, selective internal radiation therapy with yttrium-90 resin microspheres, cryoablation, radiofrequency , chemical, and microwave ablation. Candidates for SBRT are patients with unresectable liver metastatic disease and patients with comorbidities which disable surgical treatment, with adequate function of uninvolved liver tissue. Respiration induced motion of target volume can be reduced by indroduction of motion management strategies such as infrared markers, deep inspiration breath hold, abdominal compression, respiratory tracking and gating. CyberKnife, TomoTherapy machine and modified linear accelerators are used for delivering SBRT. These units allow us to deliver dose more precisely and to make dose escalation. Different regimes of fractionation are optional, from single fraction to hypofractionation regimes, and doses are typically around 30–60 Gy in 3 fractions. Low toxicity rates in patients with liver metastases treated with SBRT are in relation with precise treatment planning, dose prescription and fractionation. Results of research suggest that delivery of large doses can provide high rate of local response, but on the other hand there is possibility of disease progression out of target volumes. With adequate selection of patients with unresectable liver metastases, the implementation of SBRT, especially in combination with effective systematic treatment modalities, can provide better local control with extension of survival.
Keywords: colorectal carcinoma, liver metastases, stereotactic body radiation therapy